The role of technology in language immersion: a systematic literature review - Abdullah Syahid Robbani; Umi Baroroh; Tulus Musthofa; Sigit Purnama; Sugeng Sugiyono; Ahmad Zaki Annafiri (Institute of Advanced Engineering and Science, 2024)
Challenges and oppositions related to language immersion implementation are still ongoing, although numerous types of research have shown the positive impact provided by this program in a wide range of aspects. One of the most bulging challenges is that language learners are restrained from conducting language immersion directly in the country where the target language is spoken. To responding such challenges, the researchers, through this systematic literature review, reveal many important aspects that one should consider in achieving successful language immersion and probe the right technology that could provide an immersive language-learning environment. The researchers explored 56 articles covered in this research scope based on the inclusion criteria to answer the existing formulation of problems. The result identified the importance of the environment, the leader and teacher’s vital role in establishing the immersion program’s objective, and translating parents’ expectations when registering their children for the program. Utilizing technology such as virtual reality and games in language learning can imitate an immersive language experience. Developing other kinds of technology is required to bring a vaster preference for the parents who want to apply language immersion through technology in their children’s language learning.